KONSEP PESERTA DIDIK DALAM PANDANGAN PENDIDIKAN ISLAM: SEBUAH TINJAUAN KONSEPTUAL - Yulia, Yulia; Taqwima, Ahsani; Utami, Monita; Hendrizal, Hendrizal (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This research aims to describe students' concepts from the perspective of Islamic education. The method used in this research is a qualitative method with a literature study approach. The results of this research show that students are every human being who throughout their life is always in development. The connection with education is that the development of students is always towards maturity where everything happens because of the help and guidance provided by educators. In the educational process, a potential student is the object or goal of an educational system who directly acts as a subject or individual who needs to receive recognition from the environment in accordance with the individual's own existence.